Virtual-Reality Based Crisis Management Training for Teachers: An Overview of the VRTEACHER Project - Stavroulia, Kalliopi Evangelia; Aedo, Ignacio; Diaz, Paloma; Lanitis, Andreas (My University, 2021)
The coronavirus pandemic has created an educational crisis without precedent, posed new challenges, and highlighted the need for digital skills empowerment among teachers along with the use of technology-based approaches to support the delivery of education and ensure the future of learning. As a return to normality is far from over, the implementation of novel training approaches for teacher training is more imperative than ever. In this context, this paper presents the VRTEACHER project that aims to promote the use of digital technologies and innovative and open pedagogies as part of teachers' training methodology. The vision of the project is to empower teacher's skills (such as empathy, perspective-taking, self-efficacy, adaptability, etc.) and readiness related to class management in crisis situations, through Virtual Reality (VR) immersive and experiential training approaches that reflect real-life scenarios and situations. The aim and challenge of the project are not just to adapt the training provided to the digital era and connect it with new technologies but to build a holistic new approach to teacher training through the use of VR.
Keywords: Virtual Reality; Teacher training; VRTEACHER